Detection of co-infection of Gardnerella vaginalis and Atopobium vaginae using qualitative PCR: A better predictor of bacterial vaginosis. (June 2021) - Sehgal, Pragati Grover; Dadwal, Rajneesh; Sharma, Bhawna; Sehgal, Amit; Bagga, Rashmi; Chopra, Seema; Angrup, Archana; Yadav, Rakesh; Sharma, Nandita; Sethi, Sunil
Abstract: The present study aimed to determine the utility of detection of co-infection of Gardnerella vaginalis and Atopobium vaginae using qualitative PCR for diagnosing bacterial vaginosis (BV). Vaginal samples (n = 385) categorized as positive (n = 108) or negative (n = 208) for bacterial vaginosis based on the Nugent scoring system, were analyzed for the presence of G. vaginalis and A. vaginae by conventional PCR. We compared the sensitivity, specificity, positive predictive value, negative predictive value and odds ratio for the detection of each bacterium alone with the combination of the two bacteria for diagnosing BV. The detection of co-infection of the two bacteria demonstrated a sensitivity of 96%, a specificity of 82.9%, a positive predictive value of 68.5%, a negative predictive value of 98.2% with an odds ratio of 116 (CI -32 - 409). In our study, we found a high sensitivity, specificity, negative predictive value and odds ratio for the detection of co-infection of A. vaginae and G. vaginalis for the diagnosis of BV. Graphical abstract: Image 1 Highlights: Gardnerella vaginalis and Atopobium vaginae ; association with bacterial vaginosis. Qualitative PCR detecting co-infection of both can diagnose bacterial vaginosis. Better diagnosis can improve the management perspective of bacterial vaginosis.